"It's Us Doing It!" The Power of Participatory Action Research in Prison: A Contradiction in Terms? – Phase 1. Issue 3 (13th May 2021) - Haarmans, Maria; ,; Perkins, Elizabeth; Jellicoe-Jones, Lorna
Abstract: We describe and reflect upon the process of setting up participatory action research (PAR) with a group of men resident on a personality assessment and treatment service in a medium security prison for male offenders. The service is part of the national offender personality disorder (OPD) pathway, a joint initiative between the National Health Service England and Her Majesty's Prison & Probation Service set up in 2011. Its aim was to provide a pathway of services for offenders, likely to be diagnosed with a personality disorder, to reduce risk of re-offending and improve psychological health and wellbeing. Consistent with PAR principles, prisoners were trained as co-researchers with the aim of co-producing new knowledge and improving their community. To our knowledge, this is the first PAR project conducted within the OPD pathway. We focus here on initial stages of research design and development. By sharing our experiences, we contribute to the literature on co-production research highlighting key benefits and challenges of PAR in this setting. Key learnings such as the importance of obtaining organizational support, taking time for establishing trust, relationship-building and research training are discussed.